A confirmatory factor model for climate justice: Integrating human development and climate actions in low carbon economies - Furlan, Marcelo [UNESP]; Mariano, Enzo [UNESP] (Elsevier, 2022)
Although there is a growing interest in the concept of climate justice, both in academia and society in general, there is still no consensus regarding the best models and data to represent it. Thus, the objective of this paper is to test and statistically validate the confirmatory factor model for climate justice. To do this, we applied Confirmatory Factor Analysis (CFA), which designs and tests statistically the significance of a multidimensional theoretical construct. The main results were: a) the individual freedoms derived from the capability approach and the climate actions of adaptation and mitigation were empirically confirmed as viable perspectives for assessing climate justice; b) the theoretical constructs of human development, climate actions and climate justice can be constructed based on a set of 25 indicators; and c) the three confirmatory models were successfully tested to validate a theoretical/measurement model for climate justice. We believe that the results observed will provide policymakers and national governments with a new perspective for the alignment of different types of human development programs with climate change actions, helping them on the establishment of possible links between actions taken at the national level and the definition of global goals.
Keywords: Climate justice; Confirmatory Factor Analysis; Human development; Structural Equation Modeling; Wellbeing Economy